Front Cover: New Boron(III) Blue Emitters for All‐Solution Processed OLEDs: Molecular Design Assisted by Theoretical Modeling (Eur. J. Inorg. Chem. 17/2019). Issue 17 (25th April 2019) - Salla, Cristian A. M.; Teixeira dos Santos, Jéssica; Farias, Giliandro; Bortoluzi, Adailton J.; Curcio, Sergio F.; Cazati, Thiago; Izsák, Róbert; Neese, Frank; de Souza, Bernardo; Bechtold, Ivan H.
Abstract : The Front Cover shows the ideal cycle of prediction‐testing‐update that we try to achieve in this work, focusing on the most efficient blue‐emitting boron complex synthesized and the blue solution‐processed OLED made from it. Here, a computer is used to solve the necessary equations and model properties, which are then correlated with the experiments, envisioning applications. The artwork was designed by Jessica Toigo. More information can be found in the Full Paper by B. de Souza, I. H. Bechtold et al. For more on the story behind the cover research, see the Cover Profile .